Proyecto CONTRASTES: student media as learning spaces - Araya Rivera, Carlos (2012)
This paper outlines a teaching experience developed by the author during 20 years of academic advisory to university students from different majors, that produce different mass communication student media. These media are part of Proyecto CONTRASTES, the most permanent learning community of student communication at the Universidad de Costa Rica, that has built up a learning space for mass communication and radio production. This article summarizes the conceptual basis of the project and the main aspects of its organization.